Diversity and use of wild and non-cultivated edible plants in the Western Himalaya - Kamal Prasad Aryal; Sushmita Poudel; Ram Prasad Chaudhary; Nakul Chettri; Pashupati Chaudhary; Wu Ning; Rajan Kotru (BMC, 2018)
Abstract Background Local people in the Himalayan region use a wide range of wild and non-cultivated edible plants (WNEPs) for food, spice, medicinal, and cultural purposes. However, their availability, use, status and contribution to livelihood security are poorly documented, and they have been generally overlooked in recent agro-biodiversity conservation and management programmes. The study aimed to investigate WNEP diversity and current status in a part of the Kailash Sacred Landscape-a transboundary landscape shared by Nepal, India and PR China-in terms of collection, use, management and conservation initiatives. Methods Multiple methodologies and tools were used for data collection. A series of participatory tools (45 key informant interviews, 10 focus group discussions, a crop diversity fair, direct observation of species through a transect walk and rapid market assessments) was followed by a household survey (195 respondents) and complemented by a literature review. Results The study recorded 99 WNEPs belonging to 59 families of which 96 were angiosperms, one gymnosperm and two pteridophytes. Species were used for food, spice, medicine, rituals and income generation. Thirty-five species had multiple uses, including these: 40 species were used for fruit and 31 for vegetables. WNEPs contribute significantly to daily food requirements, especially the vegetables. The use value of Dryopteris cochleata was found highest (0.98) among frequently used vegetable species. The values of informant consensus factor were found maximum for worms in the stomach (0.99) and minimum for skin disease treatment (0.67). Nearly 85% of households depended exclusively on WNEPs for at least more than a month per year. Results on the importance and use of different species, gender roles in WNEP activities and conservation approaches are presented. Conclusions People living in the Kailash Sacred Landscape depend significantly on WNEPs, and this is especially critical in times of food shortage. The WNEPs have considerable potential as an important supplement to cultivated food crops. Farmers prioritise species with multiple use values and popular vegetables. However, there are numerous challenges and interventions needed to ensure conservation and management of species and their continued availability to support food security and local livelihoods.